BREAST FEEDING AND THE RISK OF BRONCHIAL ASTHMA IN CHILDHOOD: A SYSTEMATIC REVIEW - Setiawati, Ferianis; Prima Dewi, Anis (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Approximately 339 million children (4.3% of all patients) worldwide suffer from asthma. Multiple studies have demonstrated that exclusive lactation for the first six months of a child's life can reduce the risk and protect against allergies, including asthma, in children. Asthma and allergies are influenced by a number of variables, including breastfeeding. It is suspected that there is a relationship between breastfeeding and the occurrence of asthma. Objective: To determine the relationship between breastfeeding and the occurrence of asthma Methods: This systematic study used PRISMA guidelines, by selecting 238 keyword searches in multiple databases (PubMed, ScienceDirect, and Web of Science) on August 19, 2023. ((breastfeeding) AND (Risk) OR (Relation) OR (influence) AND (Pediatric) OR (Children) AND (Bronchial) AND (Asthma)) are used as keywords. The data obtained is extracted according to the results obtained. Results: There were 5 studies after selection was conducted, each study discussed the relationship between the benefits of breastfeeding on the occurrence of bronchial asthma in childhood. 3 cohort studies, 1 cross sectional, and 1 case series were obtained. The total sample in this study was 13,629. Age range 1 month to 6 years. Conclusion: Studies have shown that exclusive breastfeeding can reduce wheezing episodes and reduce the incidence of bronchial asthma in children up to a certain age. Exclusive breastfeeding can improve immune regulation and protect children from asthma.